The Etiopathogenic Mosaic of Suicidal Behaviour - Doinița Temelie-Olinici; Anton Knieling; Dan Vâță; Laura Gheucă-Solovăstru; Monica Neamțu; Mădălina Mocanu; Adriana-Ionela Pătrașcu; Vasile-Bogdan Grecu; Daniela-Anicuța Leca (Behavioral Sciences, 2025)
Suicidality is among the most controversial concepts in multi-disciplinary studies worldwide, regardless of the form and approach. The etiopathological variability in suicidal ideation correlates with the heterogeneity of the clinical and behavioural patterns of self-harm attempts, which significantly impact the prognosis and quality of life of patients. The main objective of the present study was to identify and outline the spectrum of factors predisposing to suicide, with the whole suite of consequences and manifestations in ideation and behaviour. In this regard, the research literature of the last decade contains numerous articles dealing with the theoretical premises pertaining to both the statistical and the profoundly psychological and philosophical dimensions of suicide. The micro-environment favouring the clinical evolution of self-harm/self-destructive thoughts and attempts to the terminal, final act integrates individual medical-biological and psychological factors into the overall social reality. Knowledge of the whole etiopathogenic amalgam with clinical-evolutionary implications allows for the development of methods and tools for the early assessment and prevention of suicidal risk. At the same time, the present study aims to qualitatively focus on the subjective motivation declared by patients regarding the internal, individual catalyst of suicidal ideation and attempts on a predominantly psycho-social coordination.